Solitary juvenile xanthogranuloma of the hypopharynx. Clinico-pathologic study in a child with β-Thalassemia Major and Cutaneous Mastocytosis. (August 2020) - de Soccio, Giulia; Savastano, Vincenzo; Minasi, Simone; Bertin, Serena; Serafini, Marta; Vittori, Tommaso; Riminucci, Mara; Corsi, Alessandro
Abstract: Juvenile Xanthogranuloma (JXG), the most common pediatric non-Langerhans cell histiocytosis, may rarely occur in association with Neurofibromatosis (types 1 and 2), Juvenile Myelomonocytic Leukemia and Cutaneous Mastocytosis (CM) and, morphologically, mimics Erdheim-Chester Disease tissue lesions and ALK-positive histiocytosis. We describe a 4-year-old girl with Beta-Thalassemia Major who developed an hypopharyngeal BRAFV600E- and ALK-negative JXG and CM. JXG has been rarely reported in the aerodigestive tract and in association with CM. In this molecular era, knowledge of genetic heterogeneity of JXG and clinical scenarios in which it may develop is essential for the appropriate diagnosis and treatment of each individual patient.